Development Of Digital-Based Teaching Materials For Freestyle Swimming Materials In PJOK Learning For Students Of Class Xi Students Of Public High School 1 Mengwi - I Made , Ardyka Putra; Ni Luh Putu , Spyanawati; Gunarto, Peby (Universitas Pendidikan Ganesha, 2024)
This study aims to develop digital-based teaching materials on basic freestyle swimming techniques in PJOK learning for class XI students of public higt school 1 Mengwi. The type of research used in this study is a type of development research using the ADDIE model. Development products are validated by learning content/material experts, learning design experts, learning media experts, and field practitioner experts. The product trial subjects of this study were individual trials by 3 students, small group trials by 7 students, and large group trials by 38 students. Data were collected using a questionnaire and the data analysis technique used was quantitative descriptive analysis. Based on the results of the feasibility test research, the percentage results of the learning content/material expert test was 95.6% very well qualified, the learning design expert test was 92.9% very well qualified, the learning media expert test was 92.2% very well qualified, the field practitioner expert test was 92.5% very well qualified. So that based on the feasibility test, it is very feasible to test the product. Product trials obtained results from individual trials of 85.9% qualified as good, small group trials of 89.0% qualified as good, and large group trials of 90.2% qualified as very good and suitable for use. The product developed in the form of digital-based teaching materials on basic freestyle swimming techniques in PJOK learning is very feasible to use for class XI students as a learning resource. Suggestions to teachers to make innovation as a basis for developing teaching materials that can increase students' interest in learning.